Cubitus varus in adults correction with lateral closing wedge osteotomy and fixation with posterior plating - Pandey, S; Shrestha, A; Dhakal, S; Neupane, G; Regmi, AP (Journal of College of Medical Sciences-Nepal, 2012)
To share the result of lateral closing wedge osteotomy and fixation with posterior reconstruction plate in correction of cubitus varus in adults. It is a retrospective case analysis of 8 cases of cubitus varus in adult treated with lateral closing wedge osteotomy through posterior triceps retracting approach. Internal fixation was done with two posterior reconstruction plates. All cases were from 15 to 29 years of age (mean 22.3 ) with 3 female and 5 male. All had cubitus varus ranging from 15- 28 deg (mean 20.16 deg) due to childhood malunited supracondylar fracture of humerus. Indication for operation was cosmetic reason only. Follow up duration was 4-22 months (mean 12.5 months). All the osteotomy united clinically in mean duration of 9 weeks ( range 8-12 weeks) with mean carrying angle 8.33 degree in postoperative phase. There was no loss of motion, no loss of fixation, no surgical site infection, nonunion or neurovascular deficit. Lateral closing wedge corrective osteotomy and fixation with posterior reconstruction plate is easy technique with satisfactory result in correction of cubitus varus in adults. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 49-53 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6839